Analisis Performa Antena Microstrip, Folded Dipole dan Open Dipole 1090 MHz Pada ADS-B Receiver Pesawat - Umi Kalsum Sania; Ade Silvia Handayani; Sarjana Sarjana; Nyayu Latifah Husni; Abdul Rahman (LPPM STIKI MALANG, 2022)
Automatic Dependent Surveillance-Broadcast (ADS-B) has a very important function for aircraft monitoring. Every aircraft in flight is equipped with a transponder that transmits twice per second altitude, position, speed, direction, and other information to ground stations and other aircraft. This tool plays a role in supporting the safety of air transportation in improving safety. In this research, the design and simulation of antenna design are carried out on the CST Studio application for microstrip antennas and the MMANA-GAL application for folded dipole and open dipole antennas. The results of the three design types were evaluated on the antenna's performance. We tested the three types' design outcomes depending on the antenna's performance. In the test data based on antenna performance, the general gain of the farthest distance parameter can be reached by the folded dipole antenna with a distance of 148.7156 km. Then followed by an open dipole antenna with a distance of 127, 0472, and the last is a microstrip antenna with a distance of 126.4916 km. At the same time, the parameter of the highest number of aircraft detected is occupied by microstrip antennas with 16 aircraft, followed by 15 open dipole antennas, and the last folded dipole antennas with 13 aircraft.